2019
DOI: 10.1182/blood-2019-129472
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Damage and Repair in Acute Myeloid Leukemia Carrying Internal Tandem Duplication of Fms-like Tyrosine Kinase 3 (FLT3-ITD) - a Mechanistic Study

Abstract: Objective Internal tandem duplication (ITD) of fms-like tyrosine kinase 3 (FLT3) is one of the most common mutations in acute myeloid leukemia (AML), occurring in nearly 30% of cases. FLT3-ITD involves in-frame duplication of 3-400 base-pairs at the juxta-membrane domain, resulting in ligand-independent activation of FLT3 signaling. Downstream effectors include activation of ERK/STAT5 via SRC kinase, activation of PI3K/AKT, phosphorylation of FOXO3A, down-regulation of equilibrative nucleoside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These effectors interact with the PI3K/Akt/mTOR pathway, elucidation of which may reveal possible mechanisms of resistance to PI3K-directed therapies. Recent studies have stressed that FLT3-ITD induces genomic instability through ROS production, which potentially contributes to chemoresistance leading to disease relapse [132,133]. The PI3K/Akt/mTOR signaling pathway is linked to both ROS production and the DNA damage response (DDR) pathway, strengthening the premise of further exploiting this pathway as a potential therapeutic target [46,134,135].…”
Section: Crosstalk Of the Pi3k/akt/mtor Signaling Pathway With Other mentioning
confidence: 99%
See 1 more Smart Citation
“…These effectors interact with the PI3K/Akt/mTOR pathway, elucidation of which may reveal possible mechanisms of resistance to PI3K-directed therapies. Recent studies have stressed that FLT3-ITD induces genomic instability through ROS production, which potentially contributes to chemoresistance leading to disease relapse [132,133]. The PI3K/Akt/mTOR signaling pathway is linked to both ROS production and the DNA damage response (DDR) pathway, strengthening the premise of further exploiting this pathway as a potential therapeutic target [46,134,135].…”
Section: Crosstalk Of the Pi3k/akt/mtor Signaling Pathway With Other mentioning
confidence: 99%
“…This concept of synthetic lethality using PARP inhibitors has been effectively examined in BRCA1-defective solid tumors, but was also exploited for the treatment hematological malignancies like AML [315][316][317]. Indeed, several in vitro studies in AML reported that PARP inhibitors induced cell cycle arrest and apoptosis, and combination with chemotherapy may induce synthetic lethality [133,318,319].…”
Section: Pi3k/akt/mtor Inhibitors In Combination With Dna Repair Inhimentioning
confidence: 99%